Adultness in children's literature: toward the awareness of adults' presence in children's literature - Semizu, Yukino (2013)
This study focuses on the notion that adults’ response to children’s literature is profoundly different from that of children, and aims to identify a pattern in texts by which adults’ response can be systematically explained. The study suggests that adults respond to certain elements in the text that resonate with their assumptions about children’s literature. On this basis, the concept of adultness is introduced to refer to these textual elements, and the way in which they can be identified in the narrative is investigated. This study concentrates on literary books, mostly published after 1960, since the issues discussed are more directly relevant to literary works than to popular fiction or classic children’s literature.